Persuasive Communication Strategies Of Property Agents In Increasing Consumer Buying Interest - Wiriyanto Wiriyanto; Muya Syaroh iwanda Lubis; Dea Amanda; Nanda Khairunnisa; Levia Hazizah; Muhammad Luthfi (Universitas Dharmawangsa Medan, 2026)
This article aims to examine persuasive communication strategies used by property agents in increasing consumer buying interest. This study uses a qualitative approach to the literature study method through the review of books and academic publications that are relevant to persuasive communication, marketing communication, the role of property agents, and consumer buying interests. The results show that persuasive communication has an important role in influencing consumer attitudes, perceptions, and purchasing interests in the property sector involving high transaction value and long-term decisions. Effective persuasive communication strategies include interpersonal approaches, clear and transparent delivery of information, tailoring messages to consumer needs, and building trust between agents and consumers. The strategy is able to reduce consumer doubts and strengthen confidence in purchasing decision making. This article concludes that persuasive communication strategies are an important factor in increasing consumer buying interest as well as building long-term relationships in property marketing